Breach of trust and repair: the impact of salespersons words and actions on buyer trust. Issue 3 (28th May 2021) - Nelson, Christopher A.; Cui, Annie Peng; Walsh, Michael F.
Abstract : Purpose: Building on prior trust repair research, this study aims to develop a more robust theoretical framework that describes trust repair strategies used by salespeople following a breach of trust. Design/methodology/approach: To achieve the aim of this paper, individual depth interviews with 18 professional salespeople, 4 sales executives and 7 purchasing agents were undertaken. Findings: This paper examines the value of using trust repair strategies (e.g. restoration, regulation and verbal repair strategies) both in isolation and in conjunction. The results suggest that individual trust repair strategies operate through impacting different dimensions of justice, as justice provides a reliable indicator as to whether the salesperson can be trusted in the future. This paper also finds that combining multiple trust repair strategies can have an additive effect on trust. Originality/value: This paper uses thematic analysis to inductively identify the effective trust repair strategies that are used by salespeople in actual exchange relationships while integrating these insights with the existing theoretical frameworks in the literature. It contributes to theory through creating a conceptual model explaining the breach of trust and trust repair process, introducing justice as a direct mediating mechanism between trust repair strategies and increased trust. The research also develops a new perspective on combining salesperson words and actions to repair trust. It also provides a managerial contribution through introducing an optimized approach to trust repair in buyer-seller relationships.